Racism in Arabic literature: Glimpses from Poetry, novel and folklore - El-Gabry, Alaa Fahti; Elaskary, Mohamed Ibrahim (Journal of Humanities & Social Sciences, 2021)
This paper discusses the idea of racism in Arabic literature. It mainly focuses on the subjective representation of black people as early as the pre-Islamic era until the modern ages. We trace the subjective representation of black people in poetry, the novel and folklore. In this paper, we do not intend we defend the Arabic culture or Arabic literature, nor do we aim to beautify the biased representation of people of color in Arabic writings. Rather, we will try to study this phenomenon in an objective and balanced way. In this regard, we would like also to reiterate the fact that the image of black people in Western literature is not in any way brighter than their depiction in Arabic literature.
Keywords: Arabic literature; Arabs; black people; race; racism